Exploring primary care physicians’ challenges in using home blood pressure monitoring to manage hypertension in Singapore: a qualitative study - Moosa, Aminath Shiwaza; Oka, Prawira; Ng, Chirk Jenn (Frontiers in Medicine, 2024)
Objective Hypertension guidelines recommend using home blood pressure (HBP) to diagnose, treat and monitor hypertension. This study aimed to explore the challenges primary care physicians (PCPs) face in using HBP to manage patients with hypertension. Method A qualitative study was conducted in 2022 at five primary care clinics in Singapore. An experienced qualitative researcher conducted individual in-depth interviews with 17 PCPs using a semi-structured interview guide. PCPs were purposively recruited based on their clinical roles and seniority until data saturation. The interviews were audio-recorded, transcribed verbatim and managed using NVivo qualitative data management software. Analysis was performed using thematic analysis. Results PCPs identified variations in patients’ HBP monitoring practices and inconsistencies in recording them. Access to HBP records relied on patients bringing their records to the clinic visit. A lack of seamless transfer of HBP records to the EMR resulted in an inconsistency in documentation and additional workload for PCPs. PCPs struggled to interpret the HBP readings, especially when there were BP fluctuations; this made treatment decisions difficult. Conclusion Despite strong recommendations to use HBP to inform hypertension management, PCPs still faced challenges accessing and interpreting HBP readings; this makes clinical decision-making difficult. Future research should explore effective ways to enhance patient self-efficacy in HBP monitoring and support healthcare providers in documenting and interpreting HBP.